Geology and geochemical variations within the eastern Lebowa Granite Suite, Bushveld Igneous Complex, South Africa: insights from fractionation and hydrothermal interference - Chauke, Rames (Frontiers in Geochemistry, 2025)
The Lebowa Granite Suite (LGS), representing the youngest component of the Bushveld Igneous Complex (BIC) magmatism, is closely associated with numerous polymetallic mineralisation assemblages. The intrusion of the LGS was accompanied by both long-lived mineralising hydrothermal systems and the concomitant reactivation of regional faults, resulting in endogranitic and exogranitic mineralisation. Despite extensive studies on the mineralisation, classification, and geochemistry of the LGS as the host rock, the different facies of the LGS have not been extensively appraised to elucidate their petrological evolution from a pristine and barren state to differentiated-metasomatised fertile phases that host polymetallic mineralisation. Hence, the current study investigated two drill cores within the eastern limb of the BIC. These cores were logged, and a total of 25 samples representing Nebo, Bobbejaankop, Klipkloof, and Lease granites were collected for petrography and whole-rock geochemical studies. The BHDD 003 drill is characteristic of Nebo granite: leucocratic, equigranular, and biotite-bearing with common perthitic alkali-feldspar and biotite minerals showing pervasive sericite and chloritic alterations, respectively. The 648 KS/1 drill intersected Bobbejaankop granite, principally hypidiomorphic, characterized by pervasive sericite and minor microcline alterations in addition to chloritized magmatic biotite and hornblende. The Bobbejaankop granite grades into Lease granite, a fine-grained variety. The Klipkloof granite, generally microgranitic but often granophyric, caps the Bobbejaankop granite at the top. The geochemical results indicate that the Nebo, Bobbejaankop, Klipkloof, and Lease granites are ferroan, calcic to alkali-calcic, peraluminous A-type, and developed within intracratonic settings. The Bobbejaankop granite shows evidence of higher fractionation than the Nebo granite, with evidence of intensive magmatic-hydrothermal alterations revealed by TEDI (Ba x (Sr/Rb)), Zr/Hf vs Y/Ho, Nb/Ta ratios, and normalised REE plots. Furthermore, the Bobbejaankop, Klipkloof, and Lease granites possess lower Zr/Hf (<∼25), indicative of higher hydrothermal affluence and consequently a higher fertility index than the Nebo granite, implying that the former granites are more likely to host endogranitic polymetallic deposits. Normalised La/Yb ratios indicate that the facies of the LGS are also cogenetic, likely emanating from the differentiation of mantle-derived alkaline mafic magma, similar to RLS, which is dominated by the removal of alkalis via subsolidus hydrothermal alteration processes.